Factors that influence customer online shopping intention among Universiti Tun Hussien Onn Malaysia (UTHM) students / Faizzatul Md Zaidon - Md Zaidon, Faizzatul (Faculty of Business Management, 2016)
The purpose of this research is to identify the factor that influences customer intention toward online shopping among Universiti Tun Hussien Onn Malaysia (UTHM) students. This research is based on a sample of 345 respondents who in Faculty of Electrical and Electronic Engineering and Faculty of Management Technology and Business Universiti Tun Hussien Onn Malaysia. The result show, there are four factors that has a significant relationship with customer online shopping intention which is internet marketing environment, product characteristic, promotional offer and trust. However, only familiarity and trust have significant influence toward customer intention on online shopping. While internet marketing environment, product characteristic and promotional offer did not have a significant influence toward customer intention on online shopping.